Urban Competitiveness: Importance, models and bases for its measurement. Towards a conceptual consensus for the new times (Cultura Económica, 2020)
Urban concentrations are key to economic and social development. In this line, the study of competitiveness at the city level and the design of strategies aimed to its enhancement is understood as an essential task by many academics and policy makers both at the regional and urban level. This strategic design involves the need to have measures that support the decision-making process and that are developed following a coherent theoretic framework or model. In this sense, this paper is concerned with the study of the competitiveness models at the regional and urban level proposed by the academic literature over the last years, with the central objective of finding elements over which some consensus could be identified in order to assist on the definition of a theoretical foundation that ultimately could be used as a tool to select -or even construct- a competitiveness model to guide competitiveness measures.
Keywords: URBAN COMPETITIVENESS; COMPETITIVENESS MODELS; CITIES